"We Enjoyed Our Childhood to The Fullest": Early Childhood Teachers' Risky Play Memories and Risky Play Managements - Sadiye Keleş; Özlem Yurt (Istanbul Kültür University, 2020)
The aim of the study is to evaluate the relationship between early childhood teachers' risky play experiences, their injury histories in their childhood and risky play management strategies they used as a teacher. 190 early childhood teachers participated in this study. Data were collected through a semi- structured interview form. Only play with great heights (climbing up a tree) and play with high speed (swinging on playground swings) were included in the semi-structured interview form. Scenario-based, black and white drawings were used as a data collection tool. Results showed that teachers' risky play histories, injury histories and their management strategies at play with great heights are independent of each other. However, a different pattern was identified for play with high speed (swinging on playground swings).  This result provides an opportunity to discuss whether teachers' injury histories at specific risky play categories, may affect their risky play management strategies.